2023
DOI: 10.3390/coatings13010212
|View full text |Cite
|
Sign up to set email alerts
|

Current Progress and Open Challenges for Combined Toxic Effects of Manufactured Nano-Sized Objects (MNO’s) on Soil Biota and Microbial Community

Abstract: Soil is a porous matrix containing organic matter and minerals as well as living organisms that vary physically, geographically, and temporally. Plants choose a particular microbiome from a pool of soil microorganisms which helps them grow and stay healthy. Many ecosystem functions in agrosystems are provided by soil microbes just like the ecosystem of soil, the completion of cyclic activity of vital nutrients like C, N, S, and P is carried out by soil microorganisms. Soil microorganisms affect carbon nanotube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 164 publications
0
6
0
Order By: Relevance
“…In acidic soils, NMs typically exist in a more active state, which increases their short-term effects. Specifically, acidic soil promotes the dissolution of Cu NMs and Ag NMs to release free ions and reduce NM aggregation (Mubeen et al, 2023). As soil pH increases, the toxicity of Ag NMs and CuO NMs toward microorganisms gradually diminishes (Schlich et al, 2018;Simonin et al, 2018).…”
Section: Key Factors Contributing To the Response Of The Soil Microbi...mentioning
confidence: 99%
“…In acidic soils, NMs typically exist in a more active state, which increases their short-term effects. Specifically, acidic soil promotes the dissolution of Cu NMs and Ag NMs to release free ions and reduce NM aggregation (Mubeen et al, 2023). As soil pH increases, the toxicity of Ag NMs and CuO NMs toward microorganisms gradually diminishes (Schlich et al, 2018;Simonin et al, 2018).…”
Section: Key Factors Contributing To the Response Of The Soil Microbi...mentioning
confidence: 99%
“…O 2 − 1 is unstable and can be converted into •OH and 1 O 2 in biological systems [ 69 ]. It can cause an imbalance of the REDOX state in the cell, resulting in oxidative damage to the organism, such as cell inflammation and death [ 70 ]. A comprehensive understanding of NP absorption mechanisms that goes beyond passive diffusion and includes endocytic pathways is required due to the complicated interactions between these components [ 71 ].…”
Section: Nanoparticle Uptake and Distribution In Plantsmentioning
confidence: 99%
“…Studies have shown that AgNPs can reduce the number of pesticides needed, but they can also be harmful to the environment. AgNPs may have several harmful environmental impacts, including ecosystem disturbance, toxicity to aquatic life, harm to soil microbial communities, and bioaccumulation [48].…”
Section: Environmental Impactsof Agnpmentioning
confidence: 99%